The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/njb.02060
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and divergence times of Onosma (Boraginaceae s.s.) based on nrDNA ITS and plastid rpl32‐trnL(UAG) and trnH–psbA sequences

Abstract: We analysed 87 species of Onosma (Boraginaceae) from throughout its distribution range to investigate its evolutionary history. Using nrDNA ITS and two plastid (rpl32‐trnL(UAG) and trnH–psbA) markers, we reconstructed phylogenetic relationships within Onosma by conducting maximum parsimony, maximum likelihood, Bayesian, and BEAST analyses. The analyses revealed that Onosma as currently circumscribed is not monophyletic. However, the vast majority of Onosma species appear to belong to a single clade, the so‐cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…et Franch., possess important medicinal values and are commonly used as the alternative of Arnebiae radix in Yunnan and its adjacent regions, China (Ge et al 2003;Chinese Pharmacopoeia Commission 2015). Until now, most of the studies on Onosma and its related genus have focused on its chemical compositions, morphological taxonomy and molecular phylogeny (Kumar et al 2013;Binzet et al 2018;Nasrollahi et al 2019); whereas, no complete chloroplast genome sequence has been reported in NCBI and other databases. Therefore, we sequenced the complete chloroplast genome sequence of the important medicinal plant, O. paniculatum, as well as reconstructed its phylogenetic tree with other groups based on cp genomes.…”
Section: Onosma Paniculatum;mentioning
confidence: 99%
“…et Franch., possess important medicinal values and are commonly used as the alternative of Arnebiae radix in Yunnan and its adjacent regions, China (Ge et al 2003;Chinese Pharmacopoeia Commission 2015). Until now, most of the studies on Onosma and its related genus have focused on its chemical compositions, morphological taxonomy and molecular phylogeny (Kumar et al 2013;Binzet et al 2018;Nasrollahi et al 2019); whereas, no complete chloroplast genome sequence has been reported in NCBI and other databases. Therefore, we sequenced the complete chloroplast genome sequence of the important medicinal plant, O. paniculatum, as well as reconstructed its phylogenetic tree with other groups based on cp genomes.…”
Section: Onosma Paniculatum;mentioning
confidence: 99%
“…and in turn, to Cystostemon Balf.f. (Weigend et al, 2009, 2013; Cecchi et al, 2011; Chacón et al, 2016, 2019; Nasrollahi et al, 2019). The genus represents a considerable evolutionary radiation, and it has controversial taxonomic treatments (Kolarčik et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The authors provided important inferences about the taxonomic and evolutionary relationships of the studied species. Taxonomic markers, like rpl32-trnL (UAG) и trnH–psbA [ 26 ], were applied successfully to different systematic groups, including the species of the Boraginaceae family. Even though these markers have some limitations, they could bring additional insight into the phylogenetic relationships among the Alkanna species.…”
Section: Introductionmentioning
confidence: 99%